Ropivacaine Infusion in Diabetics Subject with Peripheral Arterial Disease. A Prospective Study - Di Minno, M.N. D.; Milone, M.; Russolillo, A.; Lupoli, R.; Di Minno, A.; Maietta, P.; Iacovazzo, C.; Salvatore, G.; Milone, F. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Peripheral arterial disease (PAD) predicts cardiovascular and cerebrovascular ischemic events. PAD treatment is aimed at reducing clinical symptoms, local tissue loss and at preventing complications.Aims:To evaluated the effect of peridural analgesia on peripheral perfusion and pain control.In 280 diabetic subjects with severe limb ischemia (65.7% males and 34.3% females, mean age 59.3±14.4 years) with a failure of medical treatment and contraindications to endovascular and/or surgical reperfusion, we performed a 30-day long peridural ropivacaine infusion, monitoring blood pressure, VAS and ABI periodically.During ropivacaine infusion VAS significantly decreased (from 4.06±0.343 to 1.96±0.413, p<0.001). Furthermore, in the 261 (93.2%) subjects achieving a VAS value≤2 during infusion, the effect was maintained after infusion withdrawing. ABI significantly improved both during infusion (from 0.30±0.04 at baseline to 0.65±0.05 at T30, p<0.001) and after infusion withdrawing as compared with baseline values.30-day peridural analgesia with ropivacaine is a valuable therapeutic option in severe peripheral limb ischemia subjects with contraindication to surgery and with pharmacological therapy failure.
Keywords: peripheral arterial disease; Diabetes; cardiovascular risk management